Consequence Of Copper Ions On Thermal Stability Of Glucoamylase From Aspergillus Niger - Mr.S.RANGABHASHIYAM; Ms.V.VADANA SUNDARI; Ms.R.V.HEMAVATHY; Mr.K.SANKARAN (International Journal of Pharma and Bio Sciences, 2011)
The production of glucoamylase is carried out in the basal medium containing ammonium sulphate, magnesium sulphate, hydrated calcium chloride, and hydrated potassium dihydrogen phosphate by using medium optimization-Plackett Burman Design. Aspergillus niger is inoculated for the release of Glucoamylase into the surrounding medium. Then the supernatants collected by centrifugation is subjected for ammonium sulphate precipitation .Followed with this the sample is purified by using the ion exchange chromatography .The purified fractions of the sample is analyzed in SDS-PAGE. The kinetic parameters measurements for the purified sample are carried out by using starch as substrate. The purified fractions are analyzed for the effect of copper ions and it is found to have maximum activity at 5mM concentration .Then the activation energy for the native glucoamylase is 94.46 KJ/mol and the copper modified glucoamylase is 119.98 KJ/mol. The copper modified glucoamylase is found to be stable at high temperature compared to that of native enzyme.